A New Approach to the Experimental Study of Shyness: Person by Context Influences on Computer-mediated Social Communication - Brunet, Paul M. (My University, 2008)
In a series of five studies, I used the Internet and computed-mediated technologies as tools to revisit the longstanding issue within the fields of personality and experimental social psychology: "person by context" interaction on social communicative behaviour. The effects of the personality trait of shyness were examined in visually anonymous and non-anonymous conditions to see if the interaction of the person and context influenced social communication. Participants were paired in dyads and instructed to converse using a text-based online Instant Messenger program. Dyads were randomly assigned to converse with webcams or without webcams. For some types of behaviour (e.g., self-disclosure), shyness and level of visual anonymity interacted (Studies 1 and 2). Shy individuals disclosed more personal information in a visually anonymous context than a visually non-anonymous context. For non-shy individuals, self-disclosure was not influenced by the context. For other types of behaviour (e.g., affective language), the effect of shyness was consistent across context. To determine the specificity of the shyness-anonymity interaction, other person-anonymity interactions were examined (e.g., self-esteem, loneliness, sex of the participants) (Studies 3 and 4). Finally, the influence of the shyness-anonymity interaction on social communicative behaviour was examined in a cooperative performance-related task (Study 5). These series of studies suggest that anonymity is a particularly salient contextual cue for shy individuals. Furthermore, the moderating effects of anonymity on shyness do not generalize to other characteristic of the person. Instead, anonymity moderates the other characteristics (e.g., self-esteem) uniquely. The present findings have theoretical implications to the study of person by context interactions by identifying how such interactions influence specific aspects of social communication. These findings also have practical or clinical implications. For example, the treatment of social difficulties related to high shyness, low self-esteem, or high loneliness, may involve specific treatment plans building off of modifications in anonymity. Shy individuals benefit from using the Internet as a social medium in which they can control the level of anonymity as is demonstrated by their bolder behaviour during visually-anonymous conversations. The present findings also suggest that the Internet and computer-mediated technologies can be used in novel ways to study longstanding questions in personality and experimental social psychology.
Keywords: Internet, computer-mediated technologies, social psychology, communication, behaviour, self-esteem